Financial inclusion - economic growth nexus: traditional finance versus digital finance in Sub-Saharan Africa - Uche Boniface Ugwuanyi; Robinson Ugwuoke; Edith Onyeanu; Eze Festus Eze; Abner Isahaku Prince; Jude Anago; Godwin Imo Ibe (Cogent Economics & Finance, 2022)
This study examined the impact of financial inclusion on economic growth disaggregated into traditional finance and digital finance with its sub-dimension for 29 Sub-Saharan African countries, 2012-2020. The study employed the panel feasible generalised least squares and panel system generalised method of moment procedures, and the panel vector autoregression Granger causality test. The results revealed that for the full sample; (1) Both the traditional and digital financial inclusion have positive and significant impact on economic growth, (2) The impact of the traditional financial inclusion in magnitude is more than that of the digital financial inclusion which also is replicated in the access sub-dimensions, (3) Unlike the access sub-dimensions the relative impact of the usage sub-dimension shows no large difference between the traditional and the digital finance. For the sub samples divided into low-income and middle-income countries; (4) The impact of traditional and digital financial inclusion is different across income levels. Both traditional and digital finance are positive and significant in middle income countries while only digital finance is significant in low income countries, (5) Economic growth Granger caused more of traditional finance than the traditional finance Granger caused economic growth, (6) The access sub-dimension to financial services Granger caused more of economic growth than the usage sub-dimension, (7) Digital financial inclusion is neutral in middle-income countries but not in low-income countries. The study recommends that even as digital finance is the new concept in the context of a developing economy, the traditional banking structures should not be neglected.
Keywords: 330; digital financial inclusion; economic growth; financial inclusion; panel feasible generalised least squares; panel system GMM; panel VAR Granger causality test; SSA; traditional financial inclusion